Effect of Chemical Fertilization on the Impacts of Plant Growth-Promoting Rhizobacteria in Maize Crops - Nascimento, Fernanda Cristina [UNESP] (2020)
The use of chemical fertilizers strongly promotes productivity in agricultural crops; therefore, large amounts of chemical fertilizers have been used. The use of plant growth-promoting bacteria may be a strategy to reduce the use of chemical fertilizers; however, little is known about the effect of chemical fertilization on the performance of these bacteria through plant–microbe interactions. The present study aimed to verify the performance of Bacillus subtilis, Azospirillum brasilense, B. pumilus, B. amyloliquefaciens, Herbaspirillum seropedicae, Gluconacetobacter diazotrophicus, and the mixtures A. brasilense + B. subtilis, B. pumilus + B. amyloliquefaciens, and H. seropedicae + G. diazotrophicus on parameters such as nitrogen and phosphorus extraction from soil, the concentrations of these nutrients in maize plants, and plant growth in both fertilized and unfertilized soil. The results showed that H. seropedica increased the nitrogen content by 6.6 g kg−1 in leaves and 2.2 g kg−1 in the root when comparing the unfertilized with the fertilized condition. G. diazotrophicus increased the nitrogen content by 3.7 g kg−1 in leaves and 2.4 g kg−1 in the root. B. pumilus increased the phosphorous content by 1.7 g kg−1 in leaves, and B. amyloliquefaciens increased the phosphorous content by 0.61 g kg−1. The present study showed that even though the bacteria presented good performance related to plant growth under fertilized conditions, H. seropedicae, G. diazotrophicus, B. pumilus, and B. amyloliquefaciens could be used in the maize crop with a reduced chemical fertilization dose.